USE OF ENGLISH SPECIFIC INFORMATION SOURCES IN EDUCATIONAL PROCESS AS A CONDITION FOR IMPROVING OF FUTURE DENTISTS’ PROFESSIONAL COMPETENCE - O.S. Ivanytsʼka; N.I. Goncharenko; I.O. Ivanytsʼkyi; K.P. Lokes; O.P. Buhanchenko (Український стоматологічний альманах)
The need for close cooperation between different countries grows every year and necessitates the training of specialists who are fluent in languages of international communication, primarily in English, and use them in their professional activities. Today, it is difficult to imagine a competitive medical specialist who does not use knowledge of the English language in his/her activity to effectively establish professional contacts and obtain the latest information.